(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Dry sun-dried tomatoes are recommended for use in case of a lack of vitamins and microelements in the body. Sun-dried tomatoes contain fiber, which improves the motility of the digestive tract. They are excellent prevention of various vision problems. Sun-dried tomatoes help reduce the risk of blood clots in your blood vessels. This product contains serotonin - the "hormone of happiness".